PENGARUH MOTIVASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERASI DI PUSKESMAS GROBOGAN KABUPATEN GROBOGAN - Ambarwati, Ninik (Universitas Slamet Riyadi, 2015)
This study aims to find a significant effect (1) to analyze the effect of motivation on employee performance with leadership in the sub-district Puskesmas Grobogan Grobogan Grobogan; (2) to analyze a significant effect on the performance of an employee's career development in PHC Grobogan Grobogan; (3) to analyze the influence of moderate leadership career development on employee performance Grobogan sub-district Puskesmas Grobogan Grobogan. This study population is officer in Puskesmas Grobogan Grobogan as many as 70 respondents. T test results in partial regression 1 show that: 1) the variable competence (X1) significantly affects the performance of employees of sub-district Puskesmas Grobogan Grobogan Grobogan. This is shown p value of 0,000 < 0,05; 2) career development variables (X2) significantly affects employee performance Grobogan Grobogan health center, this is indicated by p value 0,017 > 0,05; 3) leadership variable (X3) did not significantly influence employee performance Grobogan Grobogan Health Center. This is shown p value of 0,072 > 0,05. The hypothesis which states that